Cell death and cell proliferation in human spina bifida. Issue Volume 106:Issue2(2015) (10th December 2015) - Avagliano, Laura; Doi, Patrizia; Tosi, Delfina; Scagliotti, Valeria; Gualtieri, Angelica; Gaston‐Massuet, Carles; Pistocchi, Anna; Gallina, Andrea; Marconi, Anna Maria; Bulfamante, Gaetano; Massa, Valentina
Abstract : Background: Spina bifida is a multifactorial congenital malformation of the central nervous system. The aim of this study was to ascertain the relevance of cell death/proliferation balance in human spina bifida and to assess autophagy distribution and levels during embryo‐fetal development in neural tissue. Methods: Five human cases with myelomeningocoele were compared with 10 healthy human controls and LC3 protein expression was also analyzed in mouse embryos. Cell death was evaluated using TUNEL (terminal deoxynucleotidyl transferase–mediated deoxyuridinetriphosphate nick end‐labeling) assay; cell proliferation was studied by counting Ki67‐positive cells, and autophagy was assessed by observing the presence of LC3 punctuate dots. Results: Comparing human cases and controls (13 to 21 weeks of gestation), we observed a significant increase in TUNEL‐positive cells in human spina bifida associated with a significantly decreased proliferation rate, indicating an alteration of the physiological cell rate homeostasis. LC3 distribution was found to be spatiotemporally regulated in both human and murine embryo‐fetuses: in early pregnancy a diffuse and ubiquitous LC3 signal was detected. After neural tube closure, an intense LC3‐positive signal, normally associated to extra energy requirement, was confined to the Lissauer's tract, the dorsolateral spinal zone containing centrally projecting axons from dorsal root ganglia, at any medullar levels. LC3 signal disappeared from 12 weeks of gestation. Conclusion: In conclusion, this study confirms the fundamental role of cell death/proliferation balance during central nervous system development and reports the changing expression of LC3 protein in mouse and human neural tube. Birth Defects Research (Part A) 106:104–113, 2016. © 2015 Wiley Periodicals, Inc.